Inferring The Cost Of Equity: Does The CAPM Consistently Outperform The Income And Multiples Valuation Models? - Moyo, Vusani; Mache, Fidelis (Journal of Applied Business Research, 2018)
A number of surveys reveal that a large number of analysts, valuation experts, investors, chief financial officers and finance academics employ the capital asset pricing model (CAPM) of Sharpe (1962) and Lintner (1965) to estimate the cost of equity. There are, however, a number of alternative valuation models that can be used to infer the cost of equity. These alternative equity valuation models include the constant growth dividend discount, the earnings and book market multiples, the residual income and the Ohlson and Juettner-Nauroth (2005) abnormal earnings growth (AEG) models. Using four mature retail firms listed on the Johannesburg Stock Exchange, this paper tested for the equivalence of these models to the CAPM in estimating the cost of equity. The study found that the variants of the constant growth dividend discount and the AEG models give similar estimates which are closer to those of the CAPM. The variants of the price-to-earnings market multiples, price-to-book market multiples, and residual income models all yield estimates that are higher than those of the CAPM. Finally, the estimates seem to be affected by the stability of the firm’s earnings and financial position.